Development of dual immunoassay for detection of mitochondrial disorders - Markkola, Laura (My University, 2021)
Mitochondrial disorders (MDs) are a large group of disorders that manifest with a wide variety of different symptoms. In addition, the lack of both sensitive and specific non-invasive biomarkers has made the detection of MDs difficult. However, recently fibroblast growth factor 21 (FGF-21) and growth differentiation factor 15 (GDF-15) have been identified as potential novel biomarkers, which could be used together to detect MDs from blood samples. The aim of this work was to study development of a dissociation-enhanced lanthanide fluorescence immunoassay (DELFIA) based dual assay for measuring FGF-21 and GDF-15 analytes, which could be used to detect MDs. Dual immunoassay was developed by determining functional antibody pairs for the analytes and testing two lanthanide chelates, Sm3+ and Eu3+, as labels. Different immunoassay protocols were tested using both labels in both dual and separated immunoassays. Finally, 84 healthy serum samples were tested in separated Eu3+ label based assays to evaluate the performance of assays. The Sm3+ label was not sensitive enough to measure biological concentrations from neither of the analytes. In separated Eu3+ label based assays with the 84 healthy samples, the GDF-15 concentrations were within or above the measurement area (1–10 ng/mL), whereas with the FGF-21 assay 29 samples were below the measurement area (<50 pg/mL). Based on the results from this study, more work is still needed to develop a functional dual immunoassay. Sensitivity of the assay would need to be improved and the assay protocol optimized. Further development of the dual immunoassay would require testing of different label options to replace the Sm3+ or antibodies with higher affinities.
Keywords: Mitochondrial disorders, FGF-21, GDF-15, dual immunoassay, DELFIA